The valorization of flotation tailings in terms of the concept of the circular economy: characterization, environmental risk assessment, and waste utilization routes: . - Mikoda, Bartosz; Potysz, Anna; Siepak, Marcin; Kmiecik, Ewa (Geology, Geophysics and Environment, 2024)
Flotation tailings originating from copper ore processing were evaluated in terms of chemical and mineralogical features, leaching, and resource potential. The results demonstrated that flotation tailings show varying degrees of the leachability of elements when exposed to different pH conditions (2–13); the Zn, Cu and Co leachabilities decrease as pH increases, whereas Mo, Ag and Sb revealed U-shaped leaching trend as a function of pH. Flotation tailings were found to be fairly reactive when exposed to water leaching and rainfall conditions. The environmental risk analysis demonstrated Zn to be the most susceptible element to liberation from the flotation tailings studied. Recovery tests demonstrated sulfuric acid to be slightly more efficient extracting agent as compared to citric acid. Hybrid approach to metal recovery was rather unsuitable for studied tailings due to lower extraction yield (not exceeding 20%) as compared to chemical treatment (not exceeding 40%).